"What's up with price controls?" Stakeholders' views on the regulation of pharmaceutical pricing in Malaysia. - Ye Shing Lourdes Loh; Audrey K L Siah; Sharon G M Koh; Wing Loong Cheong; Tin Tin Su (PLoS ONE, 2023)
Escalating costs have made the accessibility of drugs one of the biggest challenges faced by the Malaysian government. The government agreed to regulate drug prices by means of external reference pricing, but its proposed policy had a setback owing to much opposition from the pharmaceutical industry. The policy did gain support from the public and from non-governmental organisations because it ensured easy access to affordable medicines. Comments from public consultations with key stakeholders were used to explore stakeholders' perceptions of the external reference pricing policy. A total of 140 comments were analysed for this study. Stakeholders' views were classified as being from the Socioeconomic, industrial, and government sectors. To summarise, the government must carefully manage and consider stakeholders' views to ensure a sound policy. Using Mendelow's stakeholder mapping, this study mapped out stakeholders' views in a systematic approach. The classification of different stakeholders' views and recommendations led to suggestions for reviewing current practices in pharmaceutical pricing regulations in the Malaysian healthcare system. The analyses can be extended to other countries that face similar concerns.